2016
DOI: 10.1063/1.4968593
|View full text |Cite
|
Sign up to set email alerts
|

An effective electrical sensing scheme using AC electrothermal flow on a biosensor platform based on a carbon nanotube network

Abstract: We report a simple and efficient electrical sensing scheme that can be used to overcome the “diffusion limit” of affinity-based biosensors by incorporating the structural advantage of a concentric electrode biosensor platform and the microstirring effect of AC electrothermal flow (ACEF). To prove the effect of ACEF on the biosensor performance, we performed both simulations and experiments for the detection of cardiac troponin-I, which is a biomarker for acute myocardial infarction. The finite element simulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Certain strategies have been conceived that aim to speed up the detection process, some of which apply to cTnI detection techniques. Lee et al have implemented AC electrothermal flow into the design of a biosensor in an attempt to overcome the “diffusion limit” [144]. The exertion of electrokinetic forces on the fluid induces a stirring mechanism which affects small molecules, however, the response time for this biosensor remains quite high at 90 min.…”
Section: Impact Of Labelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Certain strategies have been conceived that aim to speed up the detection process, some of which apply to cTnI detection techniques. Lee et al have implemented AC electrothermal flow into the design of a biosensor in an attempt to overcome the “diffusion limit” [144]. The exertion of electrokinetic forces on the fluid induces a stirring mechanism which affects small molecules, however, the response time for this biosensor remains quite high at 90 min.…”
Section: Impact Of Labelsmentioning
confidence: 99%
“…Figure 3 and Figure 4: [37,38,48,49,50,57,58,61,65,66,68,69,70,71,74,84,85,86,87,88,89,93,94,95,96,97,104,105,111,112,115,116,117,120,121,122,123,125,126,127,128,130,132,133,134,136,138,144,145,148,150,151,159,161,174,175,176,184,185,186,187,188,189,190,…”
Section: Reprinting Figuresmentioning
confidence: 99%
“…[24] Numerical studies by Sigurdson et al further showed that electrothermally induced micro-stirring inside microchannels can improve antigen-antibody binding for flow-through assays. [25] ACEF has also been shown to enhance the performance of electrical biosensors for the detection of nucleic acids [26] and proteins; [27] however, these approaches involve multiple incubation steps requiring > 30 min and are unable to achieve single pg mL À 1 sensitivity in whole blood.…”
Section: Introductionmentioning
confidence: 99%
“…The significance of 3D nanostructured surfaces for immunoassay based current sensing was revealed by Lee et al using a field effect transistor configuration 57 . They utilized carbon nanotube networks decorated with gold nanoparticles, which acted as the actual attaching sites for the probe molecules.…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, the surface of the hydrophilic substrate, where the sensors are held, is conjugated with receptors, resulting in low quantities of binding cites on the sensor region. This is due to adhesive forces which cause the receptor assays to spread out over the sensor region 57 . Therefore, localization of the receptors on an electrode surface is the key parameter to fabricate a high-performance immunosensor.…”
Section: Introductionmentioning
confidence: 99%